Integrated Systems Pharmacology and Surface Plasmon Resonance Approaches to Reveal the Synergistic Effect of Multiple Components of Gu-Ben-Ke-Chuan Decoction on Chronic Bronchitis - Luo Z; Yu G; Wang W; Sun R; Zhang B; Wang J; Liu J; Gao S; Wang P; Shi Y (Dove Medical Press, 2021)
Zhiqiang Luo,1,* Guohua Yu,1,* Wubin Wang,1,* Rui Sun,1 Binbin Zhang,1 Jing Wang,2 Jing Liu,1 Shan Gao,1 Peng Wang,3 Yuanyuan Shi1,4 1School of Life Sciences, Beijing University of Chinese Medicine, Beijing, 102488, People’s Republic of China; 2State Key Laboratory of Natural and Biomimetic Drugs, School of Pharmaceutical Sciences, Peking University, Beijing, 100191, People’s Republic of China; 3The First Affiliated Hospital of Guangzhou Medical University, Guangzhou, 510120, People’s Republic of China; 4Shenzhen Research Institute, Beijing University of Chinese Medicine, Shenzhen, 518118, People’s Republic of China*These authors contributed equally to this workCorrespondence: Peng WangThe First Affiliated Hospital of Guangzhou Medical University, No. 151 Yanjiang Road, Yuexiu District, Guangzhou, 510120, People’s Republic of ChinaEmail mrwp0022@163.comYuanyuan ShiShenzhen Research Institute, Beijing University of Chinese Medicine, No. 16 Lanjingzhong Road, Pingshan District, Shenzhen, 518118, People’s Republic of ChinaTel +86 18565780299Email yshi@bucm.edu.cnIntroduction: Gu-Ben-Ke-Chuan (GBKC) decoction, a well-known prescription composed of seven herbs, has been widely used for treating chronic bronchitis (CB). However, the pharmacological constituents of GBKC and the underlying mechanisms by which these components act on CB remain unclear.Methods: Ultra-high-pressure liquid chromatography coupled with linear ion trap–Orbitrap tandem mass spectrometry (UHPLC-LTQ-Orbitrap) was first employed to rapidly identify compounds from GBKC. Thereafter, network pharmacology and molecular docking analyses were performed to identify the potential active constituents, candidate targets, and major pathways. Finally, the affinities between the key compounds and targets were verified via surface plasmon resonance (SPR) analysis. In addition, the anti-inflammatory effect of GBKC was verified using an LPS-induced inflammatory cell model based on the predicted results.Results: A total of 53 major compounds were identified in the GBKC decoction. After network pharmacology-based virtual screening, 141 major targets and 39 main compounds were identified to be effective in the treatment of CB. The major targets were highly enriched in the tumor necrosis factor (TNF) signaling pathway, suggesting that GBKC could attenuate the inflammatory response in patients with CB. Furthermore, molecular docking results indicated that 20 pairs of components and target proteins relevant to the TNF pathway exhibited notable interactions. Among them, eight compound-target pairs exhibited good affinity as per SPR analysis. In addition, the production of interleukin 6 and TNF-α in LPS-induced MH-S cells was suppressed after GBKC treatment.Conclusion: This study successfully clarified the mechanism of action of GBKC against CB, which demonstrated that the integrated strategy described above is reliable for identifying the active compounds and mechanisms responsible for the pharmacological activities of GBKC decoction.Keywords: Gu-Ben-Ke-Chuan decoction, chronic bronchitis, UHPLC-LTQ-Orbitrap, network pharmacology, surface plasmon resonance